Pre-clinical evaluation of a 3-nitro-1,2,4-triazole analogue of [18F]FMISO as hypoxia-selective tracer for PET. - Bejot, R; Kersemans, V; Kelly, C; Carroll, L; King, R; Gouverneur, V; Elizarov, A; Ball, C; Zhang, J; Miraghaie, R; Kolb, H; Smart, S; et al. (2010)
Hypoxia in solid tumours is associated with the promotion of various metabolic mechanisms and induces resistance to radio- and chemotherapy. Non-invasive positron emission tomography (PET) or single photon emission computed tomography by use of selective biomarkers has emerged as valuable tools for the detection of hypoxic areas within tumours so treatment can be modified accordingly. The aim of this investigation was to evaluate [(18)F]3-NTR, a 3-nitro-1,2,4-triazole analogue (N(1) substituted) of [(18)F]FMISO as a potential hypoxia selective tracer. 3-NTR and its (18)F-radiolabelled isotopic isomer were synthesised and compared with FMISO in vitro and in vivo. Their physicochemical properties were measured, the enzymatic reduction was evaluated, and the reactivity of their metabolites was investigated. Biodistribution and PET scans were performed on CBA mice bearing hypoxic CaNT tumour cells, using (18)F-labelled versions of the tracers. [(18)F]3-NTR uptake within hypoxic cells was lower than [(18)F]FMISO and [(18)F]3-NTR did not exhibit any better selectivity than FMISO as a PET tracer in vivo. Both (18)F-radiolabelled compounds are relatively evenly distributed within the whole body and the radioactive uptake within hypoxic tumours reaches a maximum at 30 min post injection and decreases thereafter. Xanthine oxidase exhibited a nitroreductase activity toward 3-NTR under anaerobic conditions, but reduced metabolites did not bind covalently. It is confirmed that 3-NTR is an electron acceptor. It is postulated that radiolabelled metabolites and fragments of [(18)F]3-NTR are freely diffusing due to their poor binding capacities. Thus [(18)F]3-NTR cannot be used as a hypoxia selective tracer for PET. The investigation provides insights into the importance of the propensity to form covalent adducts for such biomarkers.